2019
DOI: 10.1063/1.5083808
|View full text |Cite
|
Sign up to set email alerts
|

Trapping of diffusing particles by small absorbers localized in a spherical region

Abstract: We study trapping of particles diffusing in a spherical cavity with an absorbing wall containing small static spherical absorbers localized in a spherical region in the center of the cavity. The focus is on the competition between the absorbers and the cavity wall for diffusing particles. Assuming that the absorbers and, initially, the particles are uniformly distributed in the central region, we derive an expression for the particle trapping probability by the cavity wall. The expression gives this probabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…While in principle rebinding events complicate this picture, they can be renormalized into a lower effective unbinding rate [27]. Assuming that interactions between binding sites do not affect their binding to the particle of interest, the binding rate can be approximated in the presence of partially reflecting binding sites by the Smoluchowski rate [28,29] (Appendix A):…”
Section: Effective Description Of the Polymer Binding Modelmentioning
confidence: 99%
“…While in principle rebinding events complicate this picture, they can be renormalized into a lower effective unbinding rate [27]. Assuming that interactions between binding sites do not affect their binding to the particle of interest, the binding rate can be approximated in the presence of partially reflecting binding sites by the Smoluchowski rate [28,29] (Appendix A):…”
Section: Effective Description Of the Polymer Binding Modelmentioning
confidence: 99%
“…While in principle rebinding events complicate this picture, it has been showed that the period where rebindings to the same binding site occurs can be included in the time they are bound, and thus can be renormalized into a lower effective unbinding rate (Kaizu et al, 2014). Assuming that interactions between binding sites do not affect their binding to the particle of interest, the binding rate can be approximated in the presence of partially reflecting binding sites by the Smoluchowski rate (Nadler and Stein, 1996;Berezhkovskii et al, 2019) (Appendix 1):…”
Section: Effective Description Of the Polymer Bridging Modelmentioning
confidence: 99%